KONSEP MANUSIA DALAM GUNUNGAN: SEBUAH REFLEKSI FILOSOFIS TERHADAP KEARIFAN LOKAL - Andreas Yumarma (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2012)
Gunungan has important role and function in the wayang performance. Such a primacy is shown from its place in the performance which is always in the middle of the screen at the beginning and the end of performance. The colorful images of gunungan symbolize cosmic order, growth, life, and so on. Philosophical reflection of gunungan, therefore, sheds a light to the concept of human being, its existence in the world, and some ethical and religious consequences to human attitudes. There are some philosophical ideas such as structure of human existence, concept of the origin and destination of all beings (sangkan paraning dumadi), cosmic person, and human co-existence, as well as the concept of religiousity. Those concepts are topics of local wisdom in gunungan that should be reinvented in order to contribute alternative directions for both human development and societal progress.